1997
DOI: 10.1161/01.cir.96.1.61
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Low-Molecular-Weight Heparin With Unfractionated Heparin Acutely and With Placebo for 6 Weeks in the Management of Unstable Coronary Artery Disease

Abstract: Our results add to previous evidence suggesting that the low-molecular-weight heparin dalteparin administered by twice-daily subcutaneous injection may be an alternative to unfractionated heparin in the acute treatment of unstable angina or non-Q-wave myocardial infarction. Prolonged treatment with dalteparin at a lower once-daily dose in our study did not confer any additional benefit over aspirin (75 to 165 mg) alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
1
7

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(206 citation statements)
references
References 16 publications
6
192
1
7
Order By: Relevance
“…14 -17 Previous studies have shown that dalteparin, when added to aspirin, was superior to placebo but similar to unfractionated heparin for prevention of death and MI in patients with unstable angina/non-Q-wave MI. 18, 19 The ESSENCE (Efficacy and Safety of Subcutaneous Enoxaparin in Non-Q-wave Coronary Events) study reported that a brief course of therapy (median duration of treatment 2.6 days) of subcutaneous injections of enoxaparin 1.0 mg/kg every 12 hours was superior to intravenous unfractionated heparin in patients with unstable angina/non-Q-wave MI. 20 The TIMI 11A trial, a dose-ranging study, demonstrated that an initial 30-mg intravenous bolus followed by subcutaneous injections of 1.0 mg/kg enoxaparin every 12 hours was associated with a major hemorrhage rate of 1.9%, whereas a higher dose of 1.25 mg/kg every 12 hours was associated with a major hemorrhage rate of 6.5%.…”
Section: See P 1586mentioning
confidence: 99%
“…14 -17 Previous studies have shown that dalteparin, when added to aspirin, was superior to placebo but similar to unfractionated heparin for prevention of death and MI in patients with unstable angina/non-Q-wave MI. 18, 19 The ESSENCE (Efficacy and Safety of Subcutaneous Enoxaparin in Non-Q-wave Coronary Events) study reported that a brief course of therapy (median duration of treatment 2.6 days) of subcutaneous injections of enoxaparin 1.0 mg/kg every 12 hours was superior to intravenous unfractionated heparin in patients with unstable angina/non-Q-wave MI. 20 The TIMI 11A trial, a dose-ranging study, demonstrated that an initial 30-mg intravenous bolus followed by subcutaneous injections of 1.0 mg/kg enoxaparin every 12 hours was associated with a major hemorrhage rate of 1.9%, whereas a higher dose of 1.25 mg/kg every 12 hours was associated with a major hemorrhage rate of 6.5%.…”
Section: See P 1586mentioning
confidence: 99%
“…15,16 LMWHs have been investigated in several clinical circumstances, particularly the treatment of unstable angina and non-Q-wave myocardial infarction. [17][18][19][20][21] In such patients, enoxaparin has been demonstrated to be superior to UFH in preventing death, AMI, and recurrent angina, without increasing the risk of bleeding. 20,21 Despite these encouraging findings, few studies have investigated the use of LMWHs as antithrombotic adjuncts to thrombolysis.…”
mentioning
confidence: 99%
“…Dalteparin decreased the incidences of MACE such as death and AMI by 48% in the FRISC study, 23) but did not have an effect superior to that of UFH in 1,500 patients in the FRIC study. 24) In addition, dalteparin decreased MACE significantly in patients with non-Q MI, and decreased the recurrence of angina at 1-year follow-up in the ESSENCE study. 16) Furthermore, in patients with unstable angina who underwent PCI, the restenosis rate was lower in the dalteparin group than in the UFH group.…”
Section: Discussionmentioning
confidence: 92%